Development of implantable devices for continuous ambulatory monitoring of central hemodynamic values in heart failure patients. - Bennett T; Kjellstrom B; Taepke R; Ryden L (Pacing & Clinical Electrophysiology, 2005)
BACKGROUND: Care and management of patients with congestive heart failure (CHF) is a major health-care challenge. The value of acute hemodynamic data in assessing heart failure has been questioned in some studies, while more intensive hemodynamic monitoring has been reported to improve patient care in others. A series of patient studies are reported here that were conducted to identify device requirements and verify the feasibility of continuous hemodynamic monitoring in CHF patients and devices for remote transfer and use of these data. METHODS AND RESULTS: The results of four separate studies in 68 CHF patients who received systems for chronic hemodynamic monitoring between 1992 and the present are reviewed. One early study was with five patients followed for 7-16 months and another study was with nine patients followed for 4-22 months. A third study included 21 patients followed up to 39 months, and the fourth study included 32 patients implanted in 1998-99 with many of them still in follow-up. These studies support the technical feasibility of implanted devices and the external instrumentation required to transfer and manage the collected data. They also support the long-term stability and accuracy of these systems. Three additional acute studies conducted with 30 patients and chronic data from 53 of the 68 patients with the implanted systems are presented that support the feature included in the newer monitors--the ability to reliably estimate pulmonary artery diastolic pressures from the right ventricular pressure signal. CONCLUSIONS: Development of implantable technology to measure several hemodynamic variables in ambulatory CHF patients is feasible. External instrumentation needed to remotely acquire data from the implanted devices has been verified. The potential to eliminate the uncertainties associated with the use of acute, invasive hemodynamics and the ability to evaluate long-term ambulatory hemodynamic patterns is provided. These findings set the stage for determining the potential clinical value of these systems in impacting the care of chronic CHF patients.